PKMS Kampung Lele, Desa Pantai Raja, Kecamatan Perhentian Raja, Kabupaten Kampar - Novia Gesriantuti; Shabri Putra Wirman; Elsie Elsie; Israwati Harahap; Yeeri Badrun; Yulia Fitri; Nofripa Herlina (LPPM UMRI, 2020)
Partners in the Stimulus Community Partnership Program (PKMS) are RT 08 RW 02 Pantai Raja Village, Perhentian Raja District, Kampar Regency. This partner group has a business as a catfish breeder (Clarias sp.). Catfish hatchery efforts in Pantai Raja Village have started 8 years ago. However, there are problems faced by catfish farmers, namely catfish attacked by diseases and death such as fungal diseases, white spots on the body of the fish. This is thought to be caused by water quality that is not good (poisonous) as well as a lot of residual fish residue at the bottom of the pond. Based on this, the team from the Stimulus Community Partnership Program (PKMS) Muhammadiyah University of Riau (UMRI) has conducted mentoring and monitoring activities to help resolve problems from partners. The forms of activities that have been carried out are socialization and training in aquaponics making. Based on discussions with participants during the socialization and training, it can be seen that participants' knowledge of good aquaponics is felt to be very lacking.